Factors influencing students' satisfaction at Mahsa University / Wan Siti Husna W Rasir - W Rasir, Wan Siti Husna (2018)
MAHSA University establish in earnest in the year 2005 in Pusat Bandar Damansara, Damansara Heights, Kuala Lumpur with the belief that higher education in the field or healthcare is a vital component in the development of the nation. With due persistence and generous support from students, staff and the public, MAHSA is proud to announce its latest achievement of receiving University status. In Malaysia, MAHSA University have three campuses which located at Selangor, Kuala Lumpur and Sabah. MAHSA offers programs in various levels, from foundation and diploma to degree and postgraduate programs in stage as well as Healthcare Programs. Given that, the aim of this study is to examine the factors that influencing students' satisfaction at MAHSA University. The factors involved in this study are quality of university facilities, university location and university image. The data of the study are collected by using questionnaires are 362 of questionnaires will be distribute to the respondent.